Traumatic injuries of the inferior vena cava: analysis of 9 observations. Pathological, clinical and therapeutic considerations. - Cazabán Perossio, Luis A; R´íos Bruno, Guaymirán; Camaño, Mario C; Pradines, Jorge C (Cirugía del Uruguay, 2020)
Nine cases of inferior vena cava wounds with a mortality under 55 % , are dealt with. All of the patients undergoing tamponade died. Systemati; operative exploration in every instance ·of retroperitoneal hematoma is advocated. Attention is drawn to the need for preventive measures et surgery before dealing with the retroperitoneal hematoma. In cases where suture is not feasible, ligature with lesion underneath the renal veins is regarded as the procedure of choice ( case 9) . The cause of death is due to hemorrahgic shock in 90 % of cases and as a result there should be no delay in dealing with continnous bleeding and in operating prior to build-up measures since surgery is an essential p,rt of reanimation.